2015
DOI: 10.1111/hsc.12293
|View full text |Cite
|
Sign up to set email alerts
|

Cultural competence dimensions and outcomes: a systematic review of the literature

Abstract: What is known about this topic• A number of conceptual models have been developed to describe cultural competence elements.• There is no consensus regarding the components of cultural competence.• Scholars believe that cultural competence can improve patient outcomes. What this paper adds• Three major elements of cultural competence -cultural awareness, AbstractIt has been widely suggested that cultural competence is an individual's core requirement for working effectively with culturally diverse people. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
207
0
18

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(230 citation statements)
references
References 49 publications
5
207
0
18
Order By: Relevance
“…Approach to the patients who seek care shall need a good understanding and trust between the victim and health care provider, safe environment, several interviews and overcoming the barriers (language and cultural). 35,36,37 It has been shown that in the presence of culturally competent people [36][37][38] and professional interpreter [39][40][41] the chance of getting details information are more than when there is no interpreter or there was a non-professional interpreter 42…”
Section: How To Approach?mentioning
confidence: 99%
“…Approach to the patients who seek care shall need a good understanding and trust between the victim and health care provider, safe environment, several interviews and overcoming the barriers (language and cultural). 35,36,37 It has been shown that in the presence of culturally competent people [36][37][38] and professional interpreter [39][40][41] the chance of getting details information are more than when there is no interpreter or there was a non-professional interpreter 42…”
Section: How To Approach?mentioning
confidence: 99%
“…This review also revealed that cultural desire and cultural encounter/interaction were incorporated in several conceptual models and assessment tools. 14 Another literature review 15 , which included research conducted in clinics and hospital settings, examined the effectiveness of Patient Care Centered models (PCC) that incorporate a Cultural Competence perspective in improving health outcomes among culturally and linguistically diverse patients. Renzaho's literature review 15 showed evidence supporting the effectiveness of cultural competence and PCC training in increasing cultural knowledge and awareness; two of the constructs included in the CCM model.…”
mentioning
confidence: 99%
“…In another study, students gained a broader perspective on health care delivery by comparing a health care system different from that of their home country 45 . Finally, other studies found that students gained social and cultural competence, both through explicit content delivery in the didactic portion of the course and indirectly through interacting with other experts and individuals who have social and cultural experiences different from their own 46‐48 . Such awareness and knowledge are critical not only for future patient care but also in preparing the next generation of leaders in global health 49…”
Section: Discussionmentioning
confidence: 99%